1982 IEEE International Conference on Electrical Insulation 1982
DOI: 10.1109/eic.1982.7464496
|View full text |Cite
|
Sign up to set email alerts
|

The effect of absorbed oxygen on electrical treeing in polymers

Abstract: This paper describes the effect of the oxygen absorbed in the free volume of polyethylene on electr~ cal treeing phenomena. The ac tree initiation and growth were investigated at room temperature using virgin samples and also samples degassed by a vacuum pump. The tree starting voltage of the degassed samples is much higher than that of virgin samples. The exper~ mental results show this improvement can be attributed to the removal of oxygen from PE. We also observed in detail the processes of tree initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…A block of low-density polyethylene (LDPE; 0.918 g/cm 3 ) with a steel needle-shaped electrode (tip curvature of 3 mm) inserted in it was used as the experimental specimen [6]. In order to change the gases absorbed in the free volumes, the block was pretreated as shown in Table 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A block of low-density polyethylene (LDPE; 0.918 g/cm 3 ) with a steel needle-shaped electrode (tip curvature of 3 mm) inserted in it was used as the experimental specimen [6]. In order to change the gases absorbed in the free volumes, the block was pretreated as shown in Table 1.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We think that gases practically do not penetrate the crystalline phase, while the free volumes of the amorphous phase are in an equilibrium state with the atmosphere surrounding the PE and usually contain air. Figure 1 shows previously reported [4] results obtained by measurement of the change in weight of a PE block that was first kept in a vacuum for a long time to remove air from free volumes, after which it was returned to air. As air was returning to the free volumes, the weight of the block increased and, at a level of approximately 180 mg, saturation was observed.…”
Section: Free Volume and Absorbed Gasesmentioning
confidence: 98%
See 1 more Smart Citation
“…A degraded region has been found to develop around defects at high fields and this is generally taken to be the precursory step before tree and track initiation [4][5][6]. Associated studies have been largely limited to low oxygen environments [7] where aging is more pronounced. It has also been identified that degradation occurs within and around tree channels during their growth [8], however, the chemical pathways involved are again not yet known, limiting the understanding of the physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…One is the mechanism of tree initiation (including the initiation of new channels), which is related to many factors such as the electrofracture mechanics [15], charge transfer [16], photodegradation [17], the absorbed oxygen [18] and so on. The other is the mechanism of tree growth.…”
Section: Damage Caused By Pd and By Fieldmentioning
confidence: 99%